ISTRI BEKERJA DALAM RELASI SEKSUAL (Studi Pemikiran K.H. Husein Muhammad dalam Buku Fiqih Perempuan: Refleksi Kiai atas Tafsir Wacana Agama dan Gender) - Fatikhatul Khasanah (Hukum Keluarga Islam, 2022)
Actually, the issue of living or working in general is something that has been agreed upon by the scholars besides that it has also been explained explicitly by the texts of the Qur'an and Sunnah. However, when the concept of living or working is faced with a society that is different from society, such as a wife who works outside the home or domestic space. This creates a difference of opinion among the scholars. One of them is the view of wives working in sexual relations which was initiated by contemporary feminist cleric, K.H. Hussein Muhammad. Based on the above background, the writer is interested in researching and retracing the thoughts of K.H. Husein Muhammad about wives working in sexual relations and how the relevance of wives working in sexual relations today. This research is a type of library research, namely by conducting a study of two sources including primary data sources and secondary data sources. The data that the writer uses in this thesis uses qualitative data, while in analyzing this research the writer uses descriptive analytic. Based on the analysis conducted, it can be concluded that: First: the wife works outside the home according to Kiai Husein is very dependent on the considerations of both parties. If the husband is willing his wife to work, the access to sex will be lost. Because issues related to living in sexual relations need to be developed democratic attitudes and the common good. Second: Regarding wives working in sexual relations, it is relevant to today's era, namely prioritizing contextual interpretations and based on equality, benefit, and justice.